CFD modeling of rotary cement kilns - Mujumdar, Kaustubh S.; Ranade, Vivek V. (Asia-Pacific Journal of Chemical Engineering, 2008)
Rotary cement kilns are widely used to convert calcineous raw meal into cement clinker, and are key components in the cement industry. In this article, we report a comprehensive computational fluid dynamics (CFD)-based model to capture key transport processes in rotary cement kilns. Separate but coupled computational models were developed for the bed and the freeboard regions of the rotary kiln. The complex swirling airflow produced by kiln burners, coal combustion, gas-phase combustion of volatile matter and radiative heat transfer in the freeboard region were modeled. The clinkerization reactions in the bed region were modeled assuming solids as pseudo fluids. Coating formation in cement kilns (for both bed and freeboard regions) was considered. Appropriate source and sink terms were developed to model transfer of CO(2) from the bed to the freeboard region due to calcination reaction in the bed region. The developed bed and freeboard models were coupled by mass and energy communication through common interface. These coupled computational models were able to quite satisfactorily predict the available data from industrial kilns and previously published results. The computational models were also able to capture the intricacies of the burning zones of rotary cement kilns for changing burner-operational parameters like axial to swirl ratio and oxygen enrichment. The developed approach, computational models and simulation results will not only help in developing better understanding of cement kilns but also provide quantitative information about influence of burner design and other design parameters on kiln performance. (C) 2008 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: burner; CFD; coal combustion; rotary cement kiln